MARKETING COMMUNICATION AND PROMOTION IN COMPETITION WITH SOS HONEY AT MAKUKA HONEY BUSINESS - Sungkono
One of the old and classic issues in the honey business is the circulation of SOS honey (Syrup, Oplosan and Synthetic). SOS Honey is very dangerous for the health of people who consume it in the long term. The massive distribution of SOS honey in the market is due to its low price, abundant stock and low public knowledge or concern for the quality of the honey it consumes and the massive marketing. Makuka Honey, as one of the sellers of pure honey, the impact of the large number of SOS honey circulation, both the impact on the sale of honey and the negative stigma of the community on honey in the market and causing trauma to people for consuming honey. In carrying out the sale of pure honey, Makuka Honey also faces considerable challenges, such as a new brand that is not yet widely known, the price of pure honey is expensive, pure honey often runs out of stock in the field during the honey dry season.